Innovations and Perspectives of Industrial and Bioenergy Crops for Bioeconomy Development - Stolarski, Mariusz (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The production of industrial and bioenergy crops has been the subject of scientific research for many years; however, the implementation of previously proposed solutions for commercial production is still at an early stage. It should be emphasized that when developing the production of industrial and bioenergy crops on agricultural lands, it is important to avoid land-use competition with the production of food and feed. It is well justified, for initiating the sustainable production of industrial and bioenergy crops, to promote efficient species for growing on marginal lands, which are unsuitable or less suitable for food or feed production. Another important point is that industrial and bioenergy crops should include nonfood and nonfeed crops and generate agricultural products categorized as commodities and/or raw materials for industrial goods and bioenergy. These industrial and bioenergy crops can become an important source of biomass. Of course, the concept of their cultivation for nonfood (and/or nonfeed) uses is not new but, despite considerable investment in research and development, little progress has been made with regard to the introduction of such crops and their products into the market. Therefore, the papers focus on innovations and perspectives regarding sustainable industrial and bioenergy crops production, logistic chains, biomass quality, utilization and cascade biomass use for bioeconomy, socio-economic and energy analyses, etc.